Kajian Alih Fungsi Lahan Sawah Menjadi Kawasan Terbangun: Studi Kasus: Kecamatan Banyudono, Kabupaten Boyolali - Faza Fahira Sani; Yulia Asyiawati (UNISBA Press, 2022)
Abstract. The phenomenon that occurs in Banyudono District is the construction of toll exits that have an influence on the development of activities and built-up areas. This encourages the rate of conversion of agricultural land in Banyudono District and affects regional food security. The purpose of identifying the impact of rice field conversion due to the development of built-up areas in Banyudono District, Boyolali Regency. The method carried out in this study uses a quantitative approach with several analyzes including analysis of the tendency to change the function of paddy fields, and impact analysis. From the results of the analysis, it was found that the trend of development of built-up areas and the proximity of rice fields to roads triggered the conversion of rice fields in Banyudono District, as well as having an impact on socioeconomics and reducing regional food security. Abstrak. Fenomena yang terjadi di Kecamatan Banyudono terdapat pembangunan exit tol yang memberikan pengaruh terhadap pengembangan kegiatan dan kawasan terbangun. Hal ini mendorong laju konversi lahan pertanian di Kecamatan Banyudono serta berpengaruh pada ketahanan pangan wilayah. Tujuan teridentifikasinya dampak alih fungsi lahan sawah akibat perkembangan kawasan terbangun di Kecamatan Banyudono, Kabupaten Boyolali. Metode yang dilakukan pada kajian ini menggunakan pendekatan kuantitatif dengan beberapa analisis di antaranya analisis kecenderungan alih fungsi lahan sawah, dan analisis dampak. Dari hasil analisis didapat bahwa kecenderungan perkembangan kawasan terbangun dan kedekatan lahan sawah dengan jalan memicu alih fungsi lahan sawah di Kecamatan Banyudono, serta berdampak terhadap sosial ekonomi dan penurunan ketahanan pangan wilayah.